It Governance in News Company Using Cobit 5 Frameworks - Agustinus Adi Prawoto (SISFORMA, 2019)
The object of this research is PT KMN which is one of the largest media companies in Indonesia that focuses on reporting or providing the latest information on a national scale. The problem that occurs in this company is the difficulty of grouping complaints to the helpdesk and supporting divisions through the application and the success rate in returning data that does not reach 50% which makes all data that is backed up and carried out regularly becomes useless. The author conducted an audit on the Microsoft System Center 2012 R2 application to find out whether it was in accordance with business process procedures, data accuracy, and problem management. The author analyzes and chooses to use the COBIT 5 Framework in this study. The research methods carried out are interviews and direct observation in the part of the company concerned. The chosen domain is Deliver, Service and Support (DSS) which focuses on the IT process DSS01 had an average value of 2.6 and DSS02 had an average value of 2.43.